Trophic Status of the Dam Site of Koto Panjang Reservoir, Kampar district, Riau Province based on Nygaard Index - Nugroho, Rio Cahyo; Dahril, Tengku; Simarmata, Asmika H. (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Nygaard Index can be used to determined trophic state of waters. Calculation of this index is based on the number of phytoplankton species such as Chlrococcales, Centric diatom, Myxophyceae, Euglenaphyceae and Desmidiaceae. To understand the trophic state of the PLTA Koto Panjang reservoir waters, a research has been conducted in March - April 2018. There were three sampling stations, namely station 1 (an area with 100-150 floating cages), station 2 (an area with 200-300 floating cages) and station 3 (an area with 946 floating cages). In each station there were three sampling points, in the surface, 3.5 m depth, and 7 m depth. Sampling were conducted 3 times, once/week. Water quality parameter measured were phytoplankton, transparency, temperature, pH, nitrate, phosphate, Dissolved Oxygen and free carbon dioxide. Results shown that there were 82 species of phytoplankton present, namely Myxophyceae (19 species), Chlorococcales (28 species), Centric Diatom (15 species), Euglenaphyceae (1 species) and Desmidiaceae (19 species). The water quality parameters were as follows: transparency 108-138 cm, temperature 31-320C, Dissolved Oxygen 1.8-6.0 mg/L, free carbondioxide 13.8-29.5 mg/L, nitrate 0.07-0.131 mg/L, phosphate 0.15-0.36 mg/L. Nygaard Index value of the waters was 3.1-3.7, and it can be categorized as eutrophic. Â Keywords : Koto Panjang Dam, Water quality, Phytoplankton, Eutrophic